Impact of age on endothelial function of saphenous vein grafts in coronary artery bypass grafting - Saemann, Lars; Wernstedt, Lena; Pohl, Sabine; Stiller, Markus; Willsch, Jan; Hofmann, Britt; Veres, Gábor; Simm, Andreas; Szabó, Gábor (Journal of Clinical Medicine, 2023)
Background: An intact and functionally preserved endothelial layer in the graft is crucial for myocardial perfusion and graft patency after coronary artery bypass grafting (CABG). We hypothesized that old age is a risk factor for decreased endothelial function of bypass grafts. Thus, we investigated the impact of age in patients treated with CABG on endothelial function in saphenous vein grafts. Methods: We mounted the saphenous vein graft segments of CABG patients < 70 (n = 33) and ≥70 (n = 40) years of age in organ bath chambers and exposed them to potassium chloride (KCl) and phenylephrine (PE) to test the receptor-independent and -dependent contractility, followed by exposure to acetylcholine (ACh) and sodium nitroprusside (SNP) to test the endothelial-dependent and -independent relaxation. Results: The maximal contraction induced by KCl (2.3 ± 1.8 vs. 1.8 ± 2 g) was stronger in patients ≥ 70 years of age. The relative contraction induced by PE in % of KCl (167 ± 64 vs. 163 ± 59%) was similar between groups. Patients aged < 70 years showed a higher endothelial-dependent relaxation induced by acetylcholine than patients ≥ 70 years (51 ± 27 vs. 42 ± 18%). The relaxation induced by SNP was similar between both groups. Conclusions: The endothelial function of saphenous vein bypass grafts decreases during aging. Thus, age should be considered when improving graft maintenance.
Veröffentlicht: 22. August 2023
Gesehen am 25.10.2023